2019
DOI: 10.1016/j.jtcvs.2018.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous amino acid therapy for kidney protection in cardiac surgery patients: A pilot randomized controlled trial

Abstract: Objective: To determine whether a continuous intravenous infusion of standard amino acids could preserve kidney function after on-pump cardiac surgery.Methods: Adult patients scheduled to receive cardiac surgery lasting longer than 1 hour on-pump were randomized to standard care (n ¼ 36) or an infusion of amino acids initiated immediately after induction of anesthesia (n ¼ 33). The study's primary outcome measurements assessed renal function. These assessments included duration of renal dysfunction, duration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…In line with a recent pilot study [ 42 ], our results suggest that a preoperative high-oral protein load may influence renal outcomes post-cardiac surgery, even though it does not reduce the occurrence of perioperative AKI. Consistent with previous publications [ 25 ], our findings emphasize the incorporation of longer follow-up periods to determine the effects of any intervention on renal function beyond a simple reduction in perioperative AKI.…”
Section: Discussionsupporting
confidence: 88%
“…In line with a recent pilot study [ 42 ], our results suggest that a preoperative high-oral protein load may influence renal outcomes post-cardiac surgery, even though it does not reduce the occurrence of perioperative AKI. Consistent with previous publications [ 25 ], our findings emphasize the incorporation of longer follow-up periods to determine the effects of any intervention on renal function beyond a simple reduction in perioperative AKI.…”
Section: Discussionsupporting
confidence: 88%
“…This strategy, as shown in a previous study on intensive care unit patients, seems to mitigate the negative effects of cardiopulmonary bypass on kidney function. 4,5 Interestingly, the increment of nitrogenous balance derived from amino acid infusion did not result in an incremented need of continuous renal-replacement therapy, as reported by other experiences. 6 The possible efficacy of amino acids in preventing the progression of AKI is not a new finding, as the concept of renal arteriolar vasodilation, induced by amino acid infusion, was proposed 2 decades ago as a possible mechanism to improve renal perfusion.…”
supporting
confidence: 65%
“…One investigated the effect of intravenous amino acids on renal function in critically ill patients, (20) and the other investigated the protective effect of intravenous amino acids on the kidney in patients undergoing cardiac surgery. (42) The AMIGITS trial results demonstrated that amino acid intake levels of 2.0 g/kg daily were safe and that increased urea levels due to increased amino acid intake did not increase the burden on renal function( 43) but improved eGFR. The underlying mechanism may be related to the diuretic effect of amino acids.…”
Section: Discussionmentioning
confidence: 99%